Consumer Preference Testing of Boiled Sweetpotato Using Crowdsourced Citizen Science in Ghana and Uganda - Moyo, Mukani; Ssali, Reuben; Namanda, Sam; Nakitto, Mariam; Dery, Eric K.; Akansake, Daniel; Adjebeng-Danquah, Joseph; van Etten, Jacob; de Sousa, Kauê; Lindqvist-Kreuze, Hannele; Carey, Edward; Muzhingi, Tawanda (Frontiers in Sustainable Food Systems, 2021)
Crowdsourced citizen science is an emerging approach in plant sciences. The triadic comparison of technologies (tricot) approach has been successfully utilised by demand-led breeding programmes to identify varieties for dissemination suited to specific geographic and climatic regions. An important feature of this approach is the independent way in which farmers individually evaluate the varieties on their own farms as ‘citizen scientists’. In this study, we adapted this approach to evaluate consumer preferences to boiled sweetpotato (Ipomoea batatas (L.) Lam) roots of 21 advanced breeding materials and varieties in Ghana and 6 released varieties in Uganda. We were specifically interested in evaluating if a more independent style of evaluation (home tasting) would produce results comparable to an approach that involves control over preparation (centralised tasting). We compiled data from 1,433 participants who individually contributed to a home tasting (de-centralised) and a centralised tasting trial in Ghana and Uganda, evaluating overall acceptability, and indicating the reasons for their preferences. Geographic factors showed important contribution to define consumers’ preference to boiled sweetpotato genotypes. Home and centralised tasting approaches gave similar rankings for overall acceptability, which was strongly correlated to taste. In both Ghana and Uganda, it was possible to robustly identify superior sweetpotato genotypes from consumers’ perspectives. Our results indicate that the tricot approach can be successfully applied to consumer preference studies.